Effect of a tree mixture and water availability on soil nutrients and extracellular enzyme activities along the soil profile in an experimental forest - Maxwell, Tania L.; Augusto, Laurent; Bon, Lucie; Courbineau, Adèle; Altinalmazis-Kondylis, Andreas; Milin, Sylvie; Bakker, Mark R.; Jactel, Hervé; Fanin, Nicolas (Soil biology & biochemistry, 2020)
An increasing number of studies demonstrate that tree species biodiversity can affect primary productivity and nutrient cycling in forests due to several factors, such as complementarity, facilitation or selection effects. For instance, resource partitioning in soils has been found to allow a more optimized nutrient uptake in mixed species plots compared with monocultures. However, how these effects will be modified by climate change – such as water availability – is not as well understood, especially in deep soil layers. Therefore, we specifically asked how water availability may influence the effect of tree mixtures on soil microorganism activity by measuring extracellular enzyme activities (EEAs) and available nutrients along the soil profile (down to 90 cm) in a 10-year-old plantation in southwestern France, which manipulates tree species composition (Pinus pinaster and Betula pendula, in monocultures and in mixed plots) and irrigation. Our results showed that EEAs directly depend on tree species composition and water conditions in interaction with soil depth; we found a positive effect of mixing birch and pine on carbon and nitrogen-related EEAs at an intermediate soil depth (15–30 cm soil layer), while the effect of increasing water availability increased phosphorus-related EEAs mostly in the upper soil layers (0–30 cm). However, we found no significant interactive effect between tree diversity and water availability on EEAs, underlying that the negative effect of lower water availability cannot be offset by the positive effect of mixing tree species. Differences in EEAs and available nutrients along the soil profile highlight the importance to look at different soil depths to better understand how nutrient cycling may be affected by increasing tree diversity and changes in water availability. •Synergistic effect of tree diversity on C and N enzymes in the mid-soil.•Irrigation increased N and P enzyme activities in the upper soil layers.•No interaction effect between tree species composition and water availability.•Strong positive correlation between the available P and the Cenz:Penz ratio.